2014
DOI: 10.1128/jvi.00620-14
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Triple: Allied Viruses in Unique Recent Isolates of Highly Virulent Type 2 Bovine Viral Diarrhea Virus Detected by Deep Sequencing

Abstract: In February 2013, very severe acute clinical symptoms were observed in calves, heifers, and dairy cattle in several farms in North Rhine Westphalia and Lower Saxony, Germany. Deep sequencing revealed the coexistence of three distinct genome variants within recent highly virulent bovine viral diarrhea virus type 2 (BVDV-2) isolates. While the major portion (ca. 95%) of the population harbored a duplication of a 222-nucleotide (nt) segment within the p7-NS2-encoding region, the minority reflected the standard st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…However, more detailed analyses revealed that infection of cattle with BVDV-2 can be inapparent or accompanied by only mild symptoms and, vice versa, BVDV-1 is able to induce hemorrhagic disease (Lunardi, Headley, Lisboa, Amude, & Alfieri, 2008;Yesilbag et al, 2014). A very special case of fatal disease resulting from infection with a mixture of BVDV-2 was described recently (see Section 5) ( Jenckel et al, 2014).…”
Section: Bovine Viral Diarrhea and Mucosal Diseasementioning
confidence: 96%
See 2 more Smart Citations
“…However, more detailed analyses revealed that infection of cattle with BVDV-2 can be inapparent or accompanied by only mild symptoms and, vice versa, BVDV-1 is able to induce hemorrhagic disease (Lunardi, Headley, Lisboa, Amude, & Alfieri, 2008;Yesilbag et al, 2014). A very special case of fatal disease resulting from infection with a mixture of BVDV-2 was described recently (see Section 5) ( Jenckel et al, 2014).…”
Section: Bovine Viral Diarrhea and Mucosal Diseasementioning
confidence: 96%
“…Using a reverse genetics system of a BVDV-2a strain with this duplication, spontaneous deletions of this sequence were observed. A model described by the authors proposes an equilibrium between the two variants in infected animals ( Jenckel et al, 2014). It remains to be determined whether the viral variant without the duplication retains the highly virulent phenotype.…”
Section: Duplications Of Genomic Regions In Noncp Bvdv-2mentioning
confidence: 99%
See 1 more Smart Citation
“…▲ : Isolates from different clusters, but given the same name. References (I): [21,49,114,115,116]; (II): [41,49]; (III): [117]; (IV): [118]; (V): [119,120]; (VI): [52]; (VII): [21,49,121]; (VIII): [122,123,124,125,126]; (IX): [21]; (X): [127,128,129]; (XI): [21,49,130,131,132,133,134,135,136,137,138,139,140]; (XII): [141]; (XIII): [142,143]; (XIV): [144]; (XV): [21,49,52]; (XVI): [145,146]; (XVII): [21,40,147,148,149,150,151,152]; (XVIII): [153]; (XIX): [9,154,155,156]; (XX): [157,158,159,160,161,162]; (XXI): […”
Section: Figurementioning
confidence: 99%
“…Moreover, ruminant pestiviruses are genetically classified into various subtypes. To date, the viruses included in the BVDV‐1 species are differentiated into at least 20 subtypes, indicated as 1a‐1t (Giammarioli et al., ), BVDV‐2 consists of three subtypes named 2a–2c (Jenckel et al., ), and BDV includes at least eight subtypes designated BDV‐1 to BDV‐8 (Valdazo‐González et al., ; Dubois et al., ; Giammarioli et al., ; Peletto et al., ). Other pestiviruses have been isolated from batches of contaminated sheep pox virus vaccine in Tunisia and from sheep and goats in Turkey and Tunisia and genetically characterized (Thabti et al., ; Oguzoglu et al., ).…”
Section: Introductionmentioning
confidence: 99%